Terabits without fibres - Zhenyu Xie; Qi-Fan Yang (Light: Science & Applications)
Abstract A microcomb-based coherent free-space optical link achieves a record-high bandwidth of 8.21 Tbps. Novel beam stabilisation and carrier phase retrieval schemes are employed for turbulence suppression and error correction.